Strategi Kepala Sekolah dalam Meningkatkan Kompetensi Guru Pendidikan Agama Islam di MTs Negeri 6 Banyuwangi - Ashari, Hasim (Momentum : Jurnal Sosial dan Keagamaan, 2019)
Abstact: The success of an educational institution is very dependent on the leadership of the principal. Because the principal is the leader of his institution, he must be able to bring his institution towards achieving the stated goals, he must be able to see changes and be able to see a better future in the life of globalization. The principal must be responsible for the smoothness and success of all formal arrangements and management affairs for his superiors or informally to the people who have entrusted their students. The Principal must have a strategy in Increasing Teacher Competence.